Exploring the interplay between circadian rhythms and prostate cancer: insights into androgen receptor signaling and therapeutic opportunities - Hongyan Xia; Yang Zhan; Li Wang; Xiaohui Wang (Frontiers in Cell and Developmental Biology, 2024)
Circadian rhythm disruption is closely related to increased incidence of prostate cancer. Incorporating circadian rhythms into the study of prostate cancer pathogenesis can provide a more comprehensive understanding of the causes of cancer and offer new options for precise treatment. Therefore, this article comprehensively summarizes the epidemiology of prostate cancer, expounds the contradictory relationship between circadian rhythm disorders and prostate cancer risk, and elucidates the relationship between circadian rhythm regulators and the incidence of prostate cancer. Importantly, this article also focuses on the correlation between circadian rhythms and androgen receptor signaling pathways, as well as the applicability of time therapy in prostate cancer. This may prove significant in enhancing the clinical treatment of prostate cancer.